Evaluasi Program Bantuan Operasional Sekolah (BOS) di Sekolah Dasar - Wahyu Ruri Rubiyati; Bambang Ismanto (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This research aims to gather information and obtain gaps in the implementation of the school operational assistance (BOS) program to improve the quality of education. This study used a gap evaluation model (Discrepancy). The subjects of the research were the principal, the teacher (BOS treasurer), the school supervisor, the school committee, the District coordinator, and the parents of the students. Data were collected from research sites using observation techniques, document studies and interviews. Information obtained was analyzed by using the Miles and Hubermen model which included data reduction, presentation, and conclusion drawing. Based on the result of the study, there were still gaps in several aspects between implementation and standards of BOS program. Design aspect was following BOS 2019 Technical Guidelines. There was a gap at the installation stage; there were sudden and costly activities, while expenses must be adjusted to the liability letter (SPJ). At the implementation stage, there was a delay in the process of disbursing BOS, which was the main source of education funding. Thus, from the implementation stage it can be concluded that there are still gaps between the implementation of BOS with the Technical Guidelines.